Challenges and Solutions in the Implementation of Standard Operating Procedures (SOP) for Emergency Services in Community Health Centers (Puskesmas) - Aritonang, Barita (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Emergency services at Community Health Centers (Puskesmas) play a crucial role in providing first aid to patients in critical conditions before they are referred to higher-level healthcare facilities. However, the implementation of Standard Operating Procedures (SOP) for emergency services still faces various challenges, such as a lack of understanding among healthcare personnel, limited resources, high workloads, and insufficient coordination with referral hospitals. Therefore, the aim of this study is to identify the main challenges in the implementation of emergency SOPs at Puskesmas and to formulate solutions that can improve their effectiveness. The method used in this research is a descriptive study with a qualitative approach, involving interviews and observations with healthcare workers in several Puskesmas. The results show that the majority of healthcare personnel have not fully understood and optimally applied the SOPs due to a lack of training and simulation. Additionally, the limited availability of medical equipment and healthcare staff has led to delays in handling emergency cases. High workloads also become a key factor influencing adherence to the SOPs. The discussion indicates that to overcome these challenges, regular training and simulations, increased availability of medical equipment and healthcare personnel, as well as stricter monitoring and evaluation systems are necessary. Strengthening coordination with referral hospitals also becomes a strategic step to expedite the patient referral process. In conclusion, with the proper implementation of solutions, the SOPs for emergency services at Puskesmas can be improved, making emergency services more effective and efficient in saving patients' lives